Planejamento, síntese e avaliação da atividade anticolinesterásica de análogos de Piperina - (:unkn) unknown (Universidade Estadual de Goiás, 2013)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder characterized by progressive and irreversible loss of memory and cognitive functions. Is the most common cause of dementia in elderly people, accounting for about 80% of cases. Existing treatments are only symptomatic. The more modern drugs act by increasing acetylcholine levels by inhibiting the enzyme acetylcholinesterase (AChE). However, their action is not always successful, especially in advanced stages of the disease, which justifies the search for new inhibitors that are more potent and less severe adverse effects. For this, the use of molecular modeling techniques as a strategy for rational drug design is a good bet and various substances of natural origin have been used as a prototype. The objective of this study was to design and synthesize compounds with promising acetylcholinesterase from the piperine molecule after molecular docking simulations. For this, the virtual assays were performed using the program GOLD 4.1, based on the mode of interaction between donepezil and AChE due to structural similarity between this drug and piperine. Based on the results of these preliminary assays it was proposed the synthesis of a series of asymmetric azines structurally related to the prototype. Forty compounds with different substitution patterns were synthesized. The anticholinesterase activity of the substances was evaluated by in vitro microplate assay with Ellman's reagent (Method modified by Rhee). Among these compounds, 5 showed the ability to inhibit AChE, albeit with lower percentages of inhibition obtained for the piperine 12, acid 13 and piperic ester 14 which were: 46.5, 50.6 and 63.6%, respectively. In addition the antioxidant potential of the substances tested with anticholinesterase activity was evaluated by voltammetry. Of these, compounds 12, 13, 14, 46 and 47 showed electroactivity.
Keywords: Doença de Alzheimer; Acetilcolinesterase; Piperina; Docking; Azinas; Alzheimer's disease; Acetylcholinesterase; Piperine; Docking; Azines; CIENCIAS EXATAS E DA TERRA::QUIMICA